Gastric foreign bodies in a 5-year child: pattern of clinical presentations (case report) - A.S. Bevz; T.A. Bokova; L.M. Elin (LCC «Medicine-Inform», 2022)
A.S. Bevz1, T.A. Bokova1,2, L.M. Elin1 1M.F. Vladimirskiy Moscow Regional Research and Clinical Institute, Moscow,   Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Gastrointestinal foreign bodies (FB) are a relevant issue of present-day pediatrics due to non-specific clinical presentations, difficulties in collecting medical history because of child's age, and low awareness of parents and practitioners. The authors describe a 5-year girl with multiple gastric FBs (a conglomeration of hundred 0.3-cm magnetic balls). The girl was twice admitted to different hospitals with different incoming diagnoses. Non-specific clinical symptoms and complaints resulted in late diagnosis, primary exclusion of other infectious (acute gastroenteritis) and inflammatory (ulcerative colitis) GI disorders, and unreasonable prescription of medications including antibiotics. The authors address the management strategy for gastric magnetic FBs in this child and difficulties with their endoscopic removal. More than three weeks (24 days) had passed from the first symptoms to the final diagnosis. This case report illustrates the need for the accurate  collection of medical history and timely diagnostic search using X-ray and endoscopic imaging irrespective of a child's age. Keywords: foreign bodies, gastrointestinal tract, children, magnetic balls, endoscopy, X-ray. For citation: Bevz A.S., Bokova T.A., Elin L.M. Gastric foreign bodies in a 5-year child: pattern of clinical presentations (case report). Russian Journal of Woman and Child Health. 2022;5(2):173-177 (in Russ.). DOI: 10.32364/2618-8430-2022-5-2-173-177.